PHYSICAL EDUCATION STUDENTS' HISTORICAL AWARENESS: AN ANALYSIS BASED ON JORN ROSEN'S HISTORICAL LEARNING THEORY - Pereira, Mateus Camargo; Impolcetto, Fernanda Moreto [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2020)
This investigation aimed at identifying Physical Education students' types of Historical Awareness and orientation skills produced in the Massive Open Online Course on the topic History of Women's Football in Brazil. The qualitative and exploratory study produced data during the course's evaluation activity. Answers were provided to the question of a young woman named Cristina and her doubts about trying to become a professional player. The students created ten Historical Narratives according to Jorn Riisen's concept. Eight of them manifested Historical Genetic Awareness and two had the Critical type. Guiding competences included: engagement with football; building an alternative in case professionalization did not work; the perspective of a career abroad. The study provides a theoretical framework to the field that can help improve teaching of Physical Education History.
Keywords: History; Physical Education; Professional training; Education; continuing